Prevelance of helicobacter pylori infection among Turkish living in or near Stutgart Germany, and the effect of triple therapy (pantoprazole-clarithomycin-metronidzole) on Helicobacter pylori infection - Cihat ŞEN (Turkish Journal of Gastroenterology, 2019)
-